ASSESSMENT OF ANTIBIOTIC PRESCRIPTION IN PATIENTS WITH NON-PNEUMONIA ACUTE RESPIRATORY TRACT INFECTION - Sauriasari, Rani; Apriyanti, Yusna Fadliyyah; Pramono, Dito (International Journal of Applied Pharmaceutics, 2018)
Objective: The Ministry of Health (MoH) Regulation No. 30, 2014, about Health Service Standards defines the need for routine monitoring of prescribing indicators for several diseases, including non-pneumonia acute respiratory tract infection (ARI). Methods: This study compares the results of percentage analysis of the antibiotic usage in patients with non-pneumonia ARI with two methods. Medical record data from April 2016 were collected from Primary Health Care (Puskesmas) Palmerah, West Jakarta. Results: Convenience sampling indicated that 14.28% of patients with non-pneumonia ARIs used antibiotics. Simple random sampling indicated that 25% of patients with non-pneumonia ARIs used antibiotics. Differences in sample selection methods affected the final outcome (percentage of patients who used antibiotics). The tolerance limit for antibiotic use in non-pneumonia ARIs established by MoH was 20%. Conclusion: These results indicate a need for MoH guidance to pay attention to the sampling techniques used in monitoring the treatment of nonpneumonia ARIs in Primary Health Care.